Ethyl {4-[(1,5-dimethyl-2,4-dioxo-2,3,4,5-tetrahydro-1H-1,5-benzodiazepin-3 -yl)methyl]-1,2,3-triazol-1-yl}acetate - Dardouri, R.; Rodi, Y.K.; Ladeira, S.; Essassi, E.M.; Ng, S.W. (International Union of Crystallography, 2010)
In the title compound, C18H21N5O4, the diazepine ring adopts a boat conformation with the triazolylmethyl-bearing C atom as the prow and the C atoms at the ring junction as the stern.